Serum gonadotropins and estradiol levels in Turkish pubertal girls - GüvenÇ, Hüseyin; GüvenÇ, Müzehher; Berki, Rezzan (Springer India, 1990)
Serum follicle stimulating hormone (FSH), luteinizing hormone (LH) and estradiol (E2) levels were measured by radioimmunoassay in the sera of 37 healthy Turkish pubertal girls. The data show that FSH levels significantly increased from stage 2 to 3, and tented to plateau during stages 3,4 and 5, and LH and estradiol levels constantly rises with advances in sexual development and significantly correlates with pubertal stages. When the serum FSH level was compared in pre and postmenarcheal girls of the same age the level was almost identical. Adversely, LH and estradiol levels were higher in postmenarcheal girls than in premenarcheal girls. © 1990 Dr. K C Chaudhuri Foundation.
Keywords: Estradiol levels; Puberty in girls; Serum gona dotropins; Tanner staging